The Influence of Work Environment and Work Discipline on Employee Performance at PT. Pos Indonesia (Persero) - Mufidah, Anisatul (Lentera Ilmu Nusantara, 2024)
This study aims to determine the effect of the work environment and work discipline on the performance of the employees of PT. Pos Indonesia (Persero). The data collection method used in this research is using field research and library research. The data of this study used primary data obtained from the results of distributing questionnaires. The sample used is 35 employees of PT. Pos Indonesia (Persero). Data analysis used multiple linear regression analysis, t test, F test and coefficient of determination. The results of the regression and hypothesis testing show that (1) the work environment partially has a positive and significant effect on the performance of the employees at PT. Pos Indonesia (Persero). (2) Work discipline partially has a positive and significant effect on employee performance at PT. Pos Indonesia (Persero). (3) The work environment and work discipline simultaneously have a positive and significant effect on the performance of employees at PT. Pos Indonesia (Persero). The magnitude of the contribution of the influence of the work environment and work discipline on the performance of employees at PT. Pos Indonesia (Persero) is 61.6% while the remaining 38.4% is influenced by other variables not examined in this study, for example work motivation, work safety and health, job satisfaction and so on.